Adaptive MAC protocol for self-deployment of WSNs in restrictive and constrained environment - Núñez Ochoa, Moisés Aníbal (2020)
Descargue el texto completo del repositorio institucional de la Université Grenoble Alpes: https://tel.archives-ouvertes.fr/tel-02988295